Articulations of the Tomie Ohtake Institute during the pandemic time: Lumina Exhibition Virtual visit, guided by artist Mariana Palma: links to Art class remote education - Della Valentina, Andrea Aparecida; Mattos, Ivana de Macedo (Revista do Colóquio, 2021)
This article aims to revisit investigations carried out by researchers in both art and education fields with an emphasis on the study of the alignment of educational actions in museums, galleries or art institutes, to schools, such as Suano (1987), Grinspum (2000 ), Barbosa (2009) and Rebouças (2013). The study is based on what museums are for and their educational role of guided tours in person to art exhibitions to approach the relationship between the exhibition spaces and the school, based on virtual learning environment modification and adaptation caused by Covid pandemic. -19 in Brazil, forcing exhibition spaces closure. It highlights Tomie Ohtake Institute actions, which allowed Lumina exhibition virtually available, with guidelines for high school students in Art classes as propellers of a unique experience and learning.
Keywords: Tomie Ohtake Institute; art museum and school; virtual environment exhibition